2014
DOI: 10.1007/s11557-014-1008-9
|View full text |Cite
|
Sign up to set email alerts
|

Amanita heishidingensis, a new species of Amanita sect. Lepidella from China

Abstract: A new species of Amanita sect. Lepidella, A. heishidingensis, is described based on both morphological and molecular evidences. It was compared with similar species and illustrated with line drawings and photographs. This species was found in Heishiding National Nature Reserve, Guangdong Province, South China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…However, amanitas from China have been quite extensively studied (e.g., Chen et al 2014, Deng et al 2014, Li & Cai 2014, Zhang et al 2015. A recent monograph of Amanita species of TABLE 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, amanitas from China have been quite extensively studied (e.g., Chen et al 2014, Deng et al 2014, Li & Cai 2014, Zhang et al 2015. A recent monograph of Amanita species of TABLE 1.…”
Section: Introductionmentioning
confidence: 99%
“…Jamur ini umumnya dimanfaatkan sebagai bahan pangan (Gambar 7A;B) oleh masyarakat lokal dengan jenis masakan khas Belitong. Genus Amanita memiliki keragaman yang tinggi terutama di daerah tropis seperti Indonesia, Malaysia, Thailand, India, Singapura, dan bagian selatan Tiongkok (Li & Cai, 2014;Thongbai et al, 2016;Tang et al, 2017). Saat merambah, jamur ini biasanya ditemukan oleh masyarakat lokal di Belitong di lantai hutan di sekitaran berbagai macam tanaman, diantaranya adalah Schima wallichii atau dalam bahasa lokal disebut sebagai 'batang seruk'.…”
Section: Metode Penelitianunclassified
“…For example, Zhang et al (2010) reported three lethal amanitas in East Asia. Deng et al (2014) and Li and Cai (2014) each described a new Amanita species from South China. In other parts of Asia, many new specie were also found.…”
Section: Diversitymentioning
confidence: 99%